Pengembangan Gim Edukasi Chemistry Fusion pada Perangkat Bergerak menggunakan Metode Iterative And Rapid Prototyping - Annisa Hestiningtyas; Wibisono Sukmo Wardhono; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The learning methods used in the learning process in the formal education world that take place in schools are generally limited to discussions, presentations and direct explanations conducted by the teacher only. In addition, the use of instructional media used during the learning process in class can be said to be inadequate, so students tend to be passive in following the learning process. One of the subjects taught in the 2013 education curriculum at the high school level as basic material is chemistry. In the world of education in the subject of chemistry material about hydrocarbons and petroleum is needed by students who want to deepen chemistry. To help provide efforts in shaping an innovative and creative learning culture in schools through the use of digital-based learning media, namely educational games. So an educational game application was developed that focused on chemistry subjects, especially hydrocarbon and petroleum materials. The development of this educational game application applies the iterative and rapid prototyping method. Quality assurance results using black-box testing show that all functions in the Chemistry Fusion educational game application can run smoothly according to their functions. Usability test results using a questionnaire to get the calculation results with a presentation of 81.62%. The calculation results are then converted using the Likert scale interpretation reference so that it shows the parameter "Very Eligible" and can be used as a learning medium.at SMA Negeri 2 Tenggarong Seberang.